The Best of Peter Finney, Legendary New Orleans Sportswriter - Finney, Peter (Book collections on Project MUSE., 2016)
"Five times each week over the past several decades, sports fans in New Orleans began their mornings by reading local sportswriter Peter Finney. Finney?s newspaper columns?entertaining, informative, and inspiring?connected New Orleans readers to the world of sports, for nearly 70 years. From a career total of 15,000 articles, this book offers a prime selection of the very best of Finney?s writing as well as an introduction from Peter Finney, Jr."--Publisher's website.